Pengaruh Eksperimental Data Historis terhadap Persepsi Pola Ilusif pada Fenomena Pentagon Pizza Index: Peran Moderator Kecemasan Geopolitik dan Hasrat Kendali - Michael Tandya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of digital technology has enabled real-time access to geopolitical information, increasing individuals' anxiety and encouraging them to seek specific patterns within a series of random events. This experimental study aimed to examine the effect of data narrative manipulation on the perception of illusory patterns in the Pentagon Pizza Index phenomenon by investigating the moderating roles of geopolitical anxiety and individuals' desire for control. The experiment employed a between-subject post-test-only design conducted through face-to-face sessions in a controlled environment. A total of 124 participants were involved in the experiment over seven different days and were assigned to either the experimental group or the control group based on their seat numbers. Measurements were conducted using adapted versions of the Generic Conspiracist Beliefs Scale (GCBS), Fear of War Scale (FORWARS), and the Desirability of Control Scale. Data were analyzed using Andrew F. Hayes' PROCESS Macro v4.2, Model 2. The regression analysis revealed that data narrative manipulation did not significantly influence individuals' perception of illusory patterns (b = −0.1672; p = 0.5328). Furthermore, neither geopolitical anxiety (p = 0.6976) nor desire for control (p = 0.2462) significantly moderated the relationship. These findings suggest that modern society is increasingly capable of filtering circulating information through an Open-Source Intelligence (OSINT) culture, leading the Pentagon Pizza Index phenomenon to be perceived merely as an internet trend.